Endothelin receptor blockers reduce I/R-induced intestinal mucosal injury: role of blood flow - (:unkn) unknown (AMER PHYSIOLOGICAL SOC, 2002)
The aim of the present study was to assess the role of endothelin (ET) in ischemia-reperfusion (I/R)-induced mucosal injury. Mucosal permeability (Cr-51-EDTA clearance) and tissue myeloperoxidase (MPO) activity were significantly increased after 30 min of ischemia followed by 30 min of reperfusion. The I/R-induced increases in mucosal permeability and polymorphonuclear leukocyte (PMN) infiltration were significantly attenuated by pretreatments with ETA (BQ-485) and/or ETB (BQ-788) receptor antagonists. Monoclonal antibody (MAb) directed against intercellular adhesion molecule-1 (ICAM-1; MAb 1A29) and superoxide dismutase (SOD) pretreatments significantly attenuated the increased mucosal permeability and PMN infiltration in a similar manner as with ET receptor antagonists. Superior mesenteric artery blood flow was significantly reduced during the reperfusion period. Both ET receptor antagonists caused a significant rise in blood flow compared with an untreated I/R group. In conclusion, our data suggest that ETA and/or ETB receptors, ICAM-1, and superoxide play an important role in I/R-induced mucosal dysfunction and PMN infiltration. Furthermore, ET is involved in the pathogenesis of postreperfusion-induced damage and beneficial effects of ET receptor antagonism are related to an improvement of disturbed blood flow during the reperfusion period.
Keywords: mucosal permeability; mucosal injury; BQ-485; BQ-788; superoxide dismutase; ISCHEMIA-REPERFUSION; ENDOGENOUS ENDOTHELIN-1; PULMONARY-CIRCULATION; HEMORRHAGIC-SHOCK; ET(B) RECEPTORS; MECHANISMS; CLEARANCE; ARTERIAL; PATHOPHYSIOLOGY; GRANULOCYTES